MENGENALI IDENTITAS SANTUN BAHASA UMAT ALLAH DI INDONESIA - Hendarto Supatra (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Whatever the purpose, people talk or write, want to be noticed by P2. There are many ways to come into that goal, one among the others, is by trying to make his or her utterance amusing. Polite utterance makes others happy. Religion teaching on polite-ness or religion leader’s (language) etiquette tend to become the sourse of patterns to follow. In the other hand, every language/culture society also has theirown rules of that language propriety. Then, it become interesting to search that kind of culture contact. This article trys to find out a set of possible principles based on that kind of contact between Christian etiquette and Indonesian language etiquette. It is hoped that the results can be used to determine the degree of politeness of Umat Allah.